2019
DOI: 10.1088/1674-1056/ab3f98
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced spin-dependent thermopower in a double-quantum-dot sandwiched between two-dimensional electron gases*

Abstract: We study the spin-dependent thermopower in a double-quantum-dot (DQD) embedded between the left and right two-dimensional electron gases (2DEGs) in doped quantum wells under an in-plane magnetic field. When the separation between the DQD is smaller than the Fermi wavelength in the 2DEGs, the asymmetry in the dots’ energy levels leads to pronounced quantum interference effects characterized by the Dicke line-shape of the conductance, which are sensitive to the properties of the 2DEGs. The magnitude of the therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…nc/4.0/ -http://creativecommons.org/licenses/by ( system can sustain a considerable temperature difference across the junction because of this property. Among all the candidates for low-dimensional thermoelectric materials, DQDs systems are recommended for their interesting thermoelectric properties due to their scalability and high degree of tunability [10][11][12]. Thus, DQDs have already paved their way to become underlying devices of spintronics not only because of beautiful physics emerging in those systems, but, more importantly, due to possible future applications and due to the possibility of manipulation of a single spin [13][14][15].…”
mentioning
confidence: 99%
“…nc/4.0/ -http://creativecommons.org/licenses/by ( system can sustain a considerable temperature difference across the junction because of this property. Among all the candidates for low-dimensional thermoelectric materials, DQDs systems are recommended for their interesting thermoelectric properties due to their scalability and high degree of tunability [10][11][12]. Thus, DQDs have already paved their way to become underlying devices of spintronics not only because of beautiful physics emerging in those systems, but, more importantly, due to possible future applications and due to the possibility of manipulation of a single spin [13][14][15].…”
mentioning
confidence: 99%
“…In particular, electrochemical properties are very relevant to the efficiency of electro-optical conversion devices. It has been shown that impurity doping is an effective method of improving electrochemical performance [1][2][3][4]. An Al-doping ternary cathode material model based on first principles density functional theory is proposed to improve the electrochemical performance of the device (Gao et al).…”
mentioning
confidence: 99%